2007
DOI: 10.1002/msc.115
|View full text |Cite
|
Sign up to set email alerts
|

Nursing support at the onset of rheumatoid arthritis: Time and space for emotions, practicalities and self‐management

Abstract: The offer to attend a nurse clinic soon after diagnosis allowed RA patients to discuss a wide range of practical and self-management issues. However, most patients also took the opportunity and time to discuss emotional reactions and adaptations to diagnosis. The data suggest an unmet need for emotional support that a nurse clinic might be able to provide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Gaining a deeper understanding of a patients' personal experience of living with RA allows us to appreciate the context in which further decisions about their health will be made. The emotional impact of a diagnosis of RA has, similarly, been described in other studies (Cox, 2004;Hehir et al, 2008). This study adds that potential improved control of their RA is the primary reason why patients have implemented behaviour change.…”
Section: Discussionsupporting
confidence: 60%
“…Gaining a deeper understanding of a patients' personal experience of living with RA allows us to appreciate the context in which further decisions about their health will be made. The emotional impact of a diagnosis of RA has, similarly, been described in other studies (Cox, 2004;Hehir et al, 2008). This study adds that potential improved control of their RA is the primary reason why patients have implemented behaviour change.…”
Section: Discussionsupporting
confidence: 60%
“…The literature suggests that in early disease, group education does not stimulate the adoption of new self-management behaviours, or have a lasting effect on symptoms (Hammond et al, 2004;Riemsma et al, 2004), but groups could be a way of meeting informational needs at the time of diagnosis. An activity analysis of the letters sent out to family physicians from the pilot new patient support clinic indicated that strong emotions were expressed (Hehir et al, 2008); therefore, skills in managing emotions in a group setting would be vital.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to communicate with a physical-activity coach at least once a month during a year and for personal meetings every third month might have been a valuable source for clearing up different question related to the disease and body functions. It has been suggested that patients with RA value having health professionals to talk to, and receiving information and emotional support from them [50], as well as sharing and discussing distress and fears for the future [51]. However, support, praise, practical assistance and information from e.g.…”
Section: {{mentioning
confidence: 99%